A RARE CASE OF BORDERLINE MUCINOUS TUMOR OF RIGHT OVARY IN YOUNG FEMALE CHILD. A CASE REPORT - Darko Angjushev; Toni Ristovski; Marija Kotevska-Angjushev (My University, 2024)
Abstract Introduction: Borderline ovarian tumors (BOTs) are extremely rare premalignant tumors in children, with an incidence of 1% of all childhood malignancies. (1) Clinical presentation is diverse, from asymptomatic to clinically significant compression of abdominal organs, great blood vessels and urinary tract. There are few reported cases in literature. (2,3) We present a rare case of BOT in young female child, successfully treated with uneventful course. Case-Report: A 12-year-old premenarchal female was admitted on Pediatric surgery department with a history of progressive abdominal distension in the last 7 months, followed by mild dysphagia and abdominal pain. Laboratory exams and serum tumor markers were unremarkable. Magnetic resonance imaging of the abdomen revealed an encapsulated, cystic right ovarian mass with huge dimensions, (37x28x18cm) suggestive for a possible ovarian tumor. Right urethra was compressed with consecutive right kidney hydronephrosis and compression of inferior vena cava. The cyst was surgically removed in total, along with 12L of clear fluid and right ovariectomy under general a nesthesia. Invasive hemodynamic monitoring was provided as perioperative course was uneventful. Postoperative analgesia was provided with Paracetamol, Metamizole and Morphine. Enteral feeding was resumed on the 2nd postoperative day. Patient was safely discharged on the 6th postoperative day. Abdominal ultrasound showed complete resolution of the kidney hydronephrosis. Pathohistological examination showed it to be a borderline mucinous tumor of the right ovary. The patient didn’t require any chemotherapy. On the 6 mouths follow up patient was free from any recurrence. Discussion: Borderline ovarian tumor is extremely rare in children. High index of suspicion is important, since clinical presentation can be unspecific. (2,4) Every female child with long lasting abdominal distension should be early examined with imaging methods such as abdominal ultrasound or MRI. Early recognition and timely surgical excision are important to avoid significant morbidity and malignant alteration. (3) Keywords: Borderline ovarian tumor, young girl, early diagnosis, premalignancy References: 1. Xu M., Wang B, Shi Y. Borderline ovarian tumor in the pediatric and adolescent population: a clinic-pathologic analysis of fourteen cases Int J Clin Exp Pathol 2020;13(5):1053-1059. 2. Ojha P, Singh Nigam J, Deshpande A, Bal Gargade C. Epithelial ovarian tumors in a premenarchal girl: a rare case report Obstet Gynecol Sci 2017;60(5):469-472. 3. Canfarotta M, Gillan E, Balarezo F, Campbell B, Tsai A, Finck C. Diagnosis, surgical treatment and management of borderline ovarian surface epithelial neoplasms: Report of 2 cases and review of literature, Journal of Pediatric Surgery Case Reports (2014), doi: 10.1016/ epsc.2014.09.009. 4. Persano G, Severi E, Cantone N, Incerti F, Ciardini E, Noccioli B. Surgical approach to giant ovarian masses in adolescents: technical considerations Pediatric Reports 2018; 10:7752 doi: 10.4081/pr.2018.7752
Keywords: Borderline ovarian tumor; young girl; premalignancy